Responses of Amniotic Fluid Volume and Its Four Major Flows to Lung Liquid Diversion and Amniotic Infusion in the Ovine Fetus - Robertson, Patricia (2009)
We designed experiments to allow direct measurement of amniotic fluid volume and continuous measurement of lung liquid production, swallowing, and urine production in fetal sheep. From these values, the rate of intramembranous absorption was calculated. Using this experimental design, the contribution of lung liquid to the control of amniotic fluid volume was examined. Fetuses were assigned to 1 of 4 protocols, each protocol lasting 3 days: control, isovolemic replacement of lung liquid, supplementation of amniotic fluid inflow by 4 L/day, and supplementation of amniotic inflow during isovolemic replacement of lung liquid. We found no effect of lung liquid replacement on any of the known flows into and out of the amniotic fluid. Although intramembranous absorption increased greatly during supplementation, the amniochorionic function curves were not altered by isovolemic lung liquid replacement. We conclude that lung liquid does not appear to contain a significant regulatory substance for amniotic fluid volume control.